Literatur: Relevansi Gaya Kepemimpinan Transformasional Terhadap Karakteristik Pegawai Generasi Z - Alldila Putri Anwa; Marsya Meliana; Aos Koeswandi (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
Generation Z consists of people born from 1995 to 2010. This generation has been familiar with technology since childhood. The purpose of this study is to determine the relationship between transformational leadership style and characteristics of generation Z employee members. This study uses a systematic literature review to identify and analyze the transformational leadership style on the characteristics of generation Z employee members, so that it can be used as a reference for future research and to help organizations understand better what they are doing. The results show that there is a match between transformational leadership style and the characteristics of generation z who value flexibility, collaboration, and innovation, often preferring workspaces that allow social interaction. Transformational leadership style is beneficial to improve the spirit, performance and participation of generation Z in public, business and social organizations.